Gamma probe-assisted brain tumor microsurgical resection: a new technique - Osvaldo Vilela Filho; Omar Carneiro Filho (Arquivos de Neuro-Psiquiatria)
OBJECTIVES: The pioneering performance of gamma probe-assisted surgery (GPAS) for brain tumors, aiming not only an improvement of tumor detection, but mainly assurance of its complete removal and the study of the usual distribution of the 99mTc-MIBI in the brain SPECT of normal individuals. METHOD: Patient's informed consent and demonstration of the tumor by the preoperative MIBI SPECT were the inclusion criteria adopted for GPAS, which was performed in one patient with a right parietal lobe metastatic tumor. The radiotracer (99mTc-MIBI) was injected in a peripheral vein 5 hours before the operation. A tumor to-normal tissue count ratio equal to or greater than 2/1 was considered indicative of tumor. MIBI SPECT was performed in five normal individuals in a pilot study. RESULTS: The gamma probe greatly facilitated intraoperative tumor detection (tumor to-normal brain count ratio was 5/1) and indicated a small piece of residual tumor after what was thought to be a complete tumor removal, allowing its resection, which, otherwise, would have been left behind. Postoperative CT confirmed complete tumor resection. The MIBI SPECT in normal individuals showed an increased uptake by the hypophisis, choroid plexus, skull, scalp and salivary glands and absence of uptake by the normal brain tissue. There were no complications. CONCLUSION: GPAS proved to be, in this single case, a safe and reliable technique to improve brain tumor detection and to confirm the presence or absence of residual tumor.